2021
DOI: 10.1080/09638237.2021.1875412
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and mental health during COVID-19 lockdown

Abstract: Background: COVID-19 pandemic lockdown measures changed the everyday lives of people around the world. Aims: To evaluate the effects of different coping strategies on mental health during COVID-19 lockdown. Methods: A representative sample for Austria was recruited through Qualtrics V R in a period of 4 weeks after the lockdown started. Measurements were coping inventory (SCI), psychological quality of life (WHO-QOL BREF, psychological domain), well-being (WHO-5), depression (PHQ-9), anxiety (GAD-7), stress (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
2
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(153 citation statements)
references
References 51 publications
9
129
2
13
Order By: Relevance
“…Behavioral, cognitive and emotional coping strategies have been found to be helpful for dealing with negative experiences, since they reduce the burden imposed by prolonged distress, enable cognitive resources to deal with everyday stressors and allow adaptation to environmental changing and demanding situations during pandemics and natural disasters [21,22]. Furthermore, coping has been demonstrated to be a key factor for psychological well-being and mental health issues during the COVID-19 era, with problem-focused coping strategies, cognitive reappraisal, social support and avoidant coping strategies along with other coping resources such as meaning in life and social connectedness as the most commonly used coping strategies [19,20,[23][24][25][26][27][28][29][30]. A review [31] has found that all the guidelines for coping with mental problems derived from COVID-19 included tips for maintaining good mental health, descriptions of a variety of psychological skills to help people cope with their anxiety and worries and the promotion of interpersonal connection at home to generate social support.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral, cognitive and emotional coping strategies have been found to be helpful for dealing with negative experiences, since they reduce the burden imposed by prolonged distress, enable cognitive resources to deal with everyday stressors and allow adaptation to environmental changing and demanding situations during pandemics and natural disasters [21,22]. Furthermore, coping has been demonstrated to be a key factor for psychological well-being and mental health issues during the COVID-19 era, with problem-focused coping strategies, cognitive reappraisal, social support and avoidant coping strategies along with other coping resources such as meaning in life and social connectedness as the most commonly used coping strategies [19,20,[23][24][25][26][27][28][29][30]. A review [31] has found that all the guidelines for coping with mental problems derived from COVID-19 included tips for maintaining good mental health, descriptions of a variety of psychological skills to help people cope with their anxiety and worries and the promotion of interpersonal connection at home to generate social support.…”
Section: Introductionmentioning
confidence: 99%
“…Since social support reduces stress (Ozbay et al, 2007;Zhong et al, 2021), the low use of this strategy in a pandemic situation shows that the community population did not use this active coping strategy. This could be due either to the fact that they dismissed this strategy as effective, or to the fact that they did not have enough ability to seek support due to the imposed movement restrictions, when they could obtain it by telematic means (Budimir et al, 2021). This search reduction of social support was also observed in samples of health professionals (Babore et al, 2020;Vagni et al, 2020), although other studies reported an increase in the search for social emotional support (Park et al, 2020); that is, moderators explain the use of this strategy.…”
Section: Discussionmentioning
confidence: 91%
“…Future research should have among its objectives to know these moderators of the effect. On the contrary, it is verified a greater use of Positive reappraisal (cognitive attempts to build and restructure a problem in a positive way while still accepting the reality of the situation) that favors adaptation to the situation, reducing stress and/or anxiety (Budimir et al, 2021;Flesia et al, 2020;Huang et al, 2020;Jungmann & Witthöft, 2020;Skapinakis et al, 2020). Finally, the community sample used the Problem Solving strategy (behavioral attempts to take action to deal directly with the problem) equally than the normative one.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, specifically, Girma et al (2021) stated about Covid-19 Pandemic-Related Stress that coping strategies significantly helped patient with chronic disease. Coping strategies are significant predictors for mental health measures on traumatic events due to could improve positive thinking (Budimir et al, 2021) and resilience (Gori et al, 2021). Stress's positive or negative effects depend on coping strategies that individuals have in solving problems (Park et al, 2009).…”
Section: Discussionmentioning
confidence: 99%